Notes on taxonomy and distribution of Desmodium zonatum (Leguminosae: Papilionoideae) in Peninsular India - Chandramohan, K.; Swamy, J.; Naidu, M. T. (Rheedea, 2016)
Desmodium zonatum Miq. (Leguminosae: Papilionoideae), a species native to Asia and Australasia, hitherto recorded only from the Western Ghats in Peninsular India, is reported here for the first time from the Eastern Ghats of Andhra Pradesh with detailed description, colour photographs and relevant notes.